Ensuring homogeneity of regional socio-economic development: Republic of Bashkortostan case study - R. F. Gataullin; E. R. Chuvashaeva (Вестник университета, 2023)
Over the past several years, an increase in regions’ heterogeneity determined by the uneven distribution of resources, lack of effective levers of innovation management, and the growing shortage of financial resources has become one of the main features of regions’ socio-economic development. That has led to their disintegration into territories that are quite different in terms of socio-economic development. The need for the use of levers of economic regulation is specific to each territory, which means that management systems react to corresponding signals quite differently. In the article, the homogeneity of the socio-economic system, its basic element being the region, is dealt with based on the connectivity of the economy. The capacity of the flows of goods and services, development of the corresponding infrastructure, optimality of population settlement, and reasonableness of financial resources redistribution, which implies the effectiveness of their use in order to stimulate economic activities and ensure innovation, are taken into account.